2013
DOI: 10.1038/nmeth.2374
|View full text |Cite
|
Sign up to set email alerts
|

TALEN-mediated precise genome modification by homologous recombination in zebrafish

Abstract: We report gene targeting via homologous recombination in zebrafish. We co-injected fertilized eggs with transcription activator-like effector nuclease mRNAs and a donor vector with long homologous arms targeting the tyrosine hydroxylase (th) locus, and we observed effective gene modification that was transmitted through the germ line. We also successfully targeted two additional genes. Homologous recombination in zebrafish with a dsDNA donor expands the utility of this model organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
230
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(233 citation statements)
references
References 19 publications
0
230
0
3
Order By: Relevance
“…Gene targeting via non-homologous end-joining (NHEJ) has also been suggested to generate combined reporter and knockout alleles 9 . Combination of TALEN-based gene targeting with insertion of a few base pairs or transgenes using small ssDNA oligonucleotides or donor vectors with longer homologous arms was initially reported for zebrafish 10,11 and later extended to other animal models including mouse 12,13 . The mouse remains the most widely used animal model in the study of human biology and diseases.…”
mentioning
confidence: 99%
“…Gene targeting via non-homologous end-joining (NHEJ) has also been suggested to generate combined reporter and knockout alleles 9 . Combination of TALEN-based gene targeting with insertion of a few base pairs or transgenes using small ssDNA oligonucleotides or donor vectors with longer homologous arms was initially reported for zebrafish 10,11 and later extended to other animal models including mouse 12,13 . The mouse remains the most widely used animal model in the study of human biology and diseases.…”
mentioning
confidence: 99%
“…Novel approaches have been recently designed to efficiently produce animals that are genetically altered in specific genomic sequences; zinc-finger nuclease (ZFN) (8)(9)(10) and transcription activator-like effector nuclease (TALEN) (11)(12)(13)(14)(15)(16) are representative next-generation platforms for customized genomic editing in transgenic animals, as well as in cultured cells in vitro. ZFNs and TALENs containing a DNA-binding domain and Fok I nuclease domain are currently crucial tools to dissect individual gene function in complicated biological systems with targeted genetic deletions and alterations.…”
mentioning
confidence: 99%
“…More recently, the transcription activator-like effectors (TALEs) technology, a milestone in the development of zebrafish mutant and transgenic lines, has lifted the limit of loci-specific targeting. With very low off-targeting effects, TALEs were therefore the first successful genome editing method that permitted homologous-directed recombination (HDR) and NHEJ-mediated knockin in zebrafish (Bedell et al 2012;Zu et al 2013). Two reports (Chang et al 2013;Hwang et al 2013b) showed that double stranded breaks (DSB), which are simpler in design and have higher mutagenesis efficiency, could also be generated using the Crispr/Cas9 technology based on the same approach used by Bedell et al (2012).…”
Section: Crispr/cas9-mediated Knockin Approaches In Zebrafishmentioning
confidence: 99%